Status of nutritional and physical condition of football athletes - Hambali, Sumbara; Syamsudar, Bangbang; Ishak, Muchamad; Bernhardin, Dindin; Taufik, Muhamad Syamsul (Journal of Physical Education Health and Sport, 2023)
This study aims 1) To find out how much the level of nutritional status of football athletes in SSB Alexis is.  2) To find out how much the level of physical condition of football athletes in SSB Alexis is.  The research method used is a descriptive method through a survey approach.  The research instruments used to measure nutritional status and physical condition are: 1) Nutritional status using Body Mass Index, 2) Physical condition using Bleep test.  The population used in this study was the entire number of SSB Alexis U-17 players as many as 25 players. While the sample in this study was 25 SSB Alexis U-17 players. The sampling technique uses the total sampling technique.  Guided by the findings of the research results on the nutritional status  and  physical condition of SSB Alexis U-17  football athletes, several conclusions can be drawn, namely as follows: 1) Based on the results of the Body Mass Index (BMI) test conducted on 25 SSB Alexis U-17 athletes showing normal category results. 2) Based on the results of the bleep test conducted on 25 SSB Alexis U-17 athletes, it showed moderate category results.